The out of towners [videorecording (DVD)] - Hiller, Arthur; Lemmon, Jack; Dennis, Sandy, 1937-1992; Baron, Sandy, 1936-2001 (Paramount, 2017)
A man from Ohio and his wife visit New York for him to interview for a big promotion, and undergo a number of adventures.